Tinjauan Regulasi dan Kebijakan dalam Pengembangan Green jobs di Indonesia - Nasri, Muhamad Azami; Keindahan, Bening Kalimasada Aura (Jurnal Ilmu Kesejahteraan Sosial, 2024)
Green jobs have become a new trend in recent years, as they are needed by various industrial sectors. Regulatory support is a key aspect in mainstreaming green jobs. Green jobs are typically associated with occupations that contribute to preserving or restoring the environment, both in traditional sectors such as manufacturing and construction, as well as in emerging green sectors like renewable energy and energy efficiency. This research aims to describe the regulatory framework in the development of green jobs in Indonesia. It is a descriptive qualitative study that primarily relies on secondary data, reviewing regulations related to green jobs. Additionally, this research is supplemented by other literature sources such as journal articles, books, institutional publications, and websites. The results show that there is no specific and integrated regulation in Indonesia for the development of green jobs. Furthermore, policy implementation largely focuses on the integration of environmental issues in general and is predominantly driven by the central government, with a top-down approach. The recommendation of this research emphasizes the importance of having specific and targeted regulations that include standards related to green jobs. Moreover, it calls for a policy framework that is not only top-down oriented but also incorporates a bottom-up approach to foster more inclusive collaboration between various stakeholders, both state and non-state actors, in promoting green job sectors across Indonesia.